Caçadores de empreendedorismo: plano de aplicação transmídia para a geração Z - Batista, Sabrina Tomaz (2017)
Increasingly startups and entrepreneurship have gained prominence in the business world and also the dreams and desires of young people. Having the business itself and putting innovative ideas into practice has made entrepreneurs risk opening their businesses. The success and profitability are the dream of those who are enterprising, but often this path requires dedication, planning and care. How then transmit the tips and knowledge to the younger ones on entrepreneurship to achieve success with their startups? It is from this question that the application plan "Hunters for Entrepreneurship" is born, a project created to address the universe of new business for Generation Z. Through the language of the transmedia narrative, and based on the typical characteristics and interests of digital natives, a plan was created that combines the audiovisual language to show the tips and contents presented by four entrepreneurs in different phases of their startups. Structured in videos, vlogs and texts, the plan also provides with a Startups Aggregator to make the meeting between entrepreneurs and large companies faster and more effective. The report presents how the construction and development of the application plan was developed. The report shows the steps plan planning, transmedia universe and selected products to make the implementation of the new enterprise safer and effective business.